Amazon Web Services : basics - Fraas, David; Safari eBooks ([Place of publication not identified] : [Stone River eLearning], 2018)
"This course will introduce students to Amazon Web Services, as well as teach them about services and support, creation of AWS account, security services , Roles, Policies, and best practices, net and content delivery, storage overview, Object Lifecycle, Versioning, and Permissions , EC2 over view, Instance Types and AMI, EBS and Snapshots."--Resource description page.
Presenter, David Fraas.
Title from title screen (viewed March 28, 2018).
Imprint from resource description page.
Keywords: Amazon Web Services (Firm); Web services; Cloud computing -- Security measures; Electronic books